Islamic finance sustainability role in Bosnia and Herzegovina - Omercic, Jasmin (Islamic Finance News, 2023)
Islamic financing is a major objective of the agenda of the SDGs globally which simply is at par with the Maqasid (higher objectives of Shariah) approach of the global Islamic banking and finance industry. It reflects the Islamic economic philosophy of entrepreneurship, assetbased development and value creation in the economy. Bosna Bank International (BBI) has maintained Islamic financing lines in Bosnia & Herzegovina (B&H) in collaboration with the Canton Sarajevo government for industry players up to more than RM5.1 million (US$1.07 million) per business at no cost.